Different techniques of steel jacketing for retrofitting of different types of concrete beams after elevated temperature exposure. (December 2020) - Aldhafairi, Faisal; Hassan, Ahmed; Abd-EL-Hafez, L.M.; Abouelezz, A.E.Y.
Abstract: Experimental and theoretical programs are designed to investigate the effect of elevated temperature on Normal (NC), high strength (HSC) and self-compacting concrete (SCC) beams. Six steel jacket techniques designed to ass the efficiency of retrofitting after elevated temperature exposure. The more effective jacket was used for different types of concrete beams. Different beams subjected to two levels of temperature 400 °C and 600 °C for 120 min. The main parameters were steel jacket angels' size, angles orientations and positions while different confinement techniques were fillet welded steel plate and threaded bars. Steel plate retrofitting did not have a significance improvement while steel angels had a good behavior as steel jacketing. The steel jacketing especially four angles improve normal concrete beams by 280% and 160% while improve self-compacting concrete by 290% and 240% after exposed to 400 °C and 600 °C respectively. The outside orientation of top angels report acceptable behavior for beams capacity restore less than 10%. The welded plates have good results than bolts in this study.